Animal Rights and the Problem of r-Strategists - Johannsen, Kyle (Ethical theory and moral practice, 2017)
Wild animal reproduction poses an important moral problem for animal rights theorists. Many wild animals give birth to large numbers of uncared-for offspring, and thus child mortality rates are far higher in nature than they are among human beings. In light of this reproductive strategy - traditionally referred to as the r-strategy - does concern for the interests of wild animals require us to intervene in nature? In this paper, I argue that animal rights theorists should embrace fallibility-constrained interventionism: the view that intervention in nature is desirable but should be constrained by our ignorance of the inner workings of ecosystems. Though authors sometimes assume that large-scale intervention requires turning nature into an enormous zoo, I suggest an alternative. With sufficient research, a new form of gene editing called CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) promises to one day give us the capacity to intervene without perpetually interfering with wild animals liberties.